The Italian Version of the Escapism Social Media Scale (ESMS): Adaptation, Validation, and Psychometric Evaluation. - Soraci, Paolo; Bevan, Nadia; Pisanti, Renato; Servidio, Rocco; Liberati, Claudia; Griffiths, Mark D. (International Journal of Mental Health & Addiction, 2026)
The present study evaluated the psychometric properties of the Italian version of the newly developed Escapism Social Media Scale (ESMS). Construct validity, convergent validity, and discriminant validity of the ESMS were analyzed with other related constructs such as coping strategies, fear of missing out (FoMO), problematic social media use (PSMU), mental well-being (MWB), and psychological distress. A convenience sample of Italian participants (N = 406, 84.48% female) completed an online survey. Confirmatory factor analyses supported the original factor structure of ESMS, and the observed variables loaded highly on the same underlying factor. The reliability was also satisfactory, demonstrating that the Italian ESMS possesses very good internal consistency (Cronbach's alpha = 0.89; McDonald's omega = 0.90). The validity of the Italian ESMS was supported by its relationships with coping strategies, FoMO, PSMU, psychological distress, and MWB. The results of the present study enrich the understanding of escapism through social media and provide Italian clinicians and researchers with a useful instrument to assess and address problems related to escapism in social media use contexts.